2017
DOI: 10.1177/2333794x17744140
|View full text |Cite
|
Sign up to set email alerts
|

Time to Drug-Resistant Tuberculosis Treatment in a Prospective South African Cohort

Abstract: This study examined time to treatment initiation by age among a prospective cohort with drug-resistant tuberculosis (DR-TB). Participants aged 13 years or older nested within a cluster-randomized trial in 2 South African provinces were evaluated. Outcomes were treatment initiation within 5 days of DR-TB diagnosis (National Tuberculosis Program guidelines) and days from diagnosis to treatment. A total of 521 participants met inclusion criteria. Eighty-two patients (16%) met national guidelines; median time to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Additionally, we did not have laboratory data to further investigate CD4 count and HIV viral loads to understand how each of those play a role in TB treatment outcomes [ 49 ]. We also were unable to assess timing of treatment initiation for either TB or HIV—both of which can have significant impact on treatment outcomes [ 6 , 50 ]. Similarly, we do not know how many (if any) of the people living with HIV not on ART may have started ART during their TB treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we did not have laboratory data to further investigate CD4 count and HIV viral loads to understand how each of those play a role in TB treatment outcomes [ 49 ]. We also were unable to assess timing of treatment initiation for either TB or HIV—both of which can have significant impact on treatment outcomes [ 6 , 50 ]. Similarly, we do not know how many (if any) of the people living with HIV not on ART may have started ART during their TB treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Geographical location of the DR-TB facility emerged as a major factor in DR-TB treatment initiation and timeliness in our study, similar to other studies in sub-Saharan Africa (SSA). [2426] Patients in some regions were half as likely to be ever initiated on treatment as those in the SW region. Timeliness of treatment did not vary significantly except for two States (Lagos and Osun) where patients were up to 10 times less likely to be treated within 1 month.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study on prison inmates in the Kyrgyz Republic reported median delays from diagnosis to starting treatment of 7 days and further delays in people with RR-TB [ 17 ]. In other settings, despite the introduction of Xpert MTB/Rif technology, median treatment delay ranged from 8 days in Ethiopia to 11 and 14 days in South Africa [ 18 , 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%